From psychotherapy to emotional well being - Deurzen, Emmy van (2012)
This paper considers the relevance of philosophy to psychotherapy. It traces the progression of early western philosophy in its approach to human emotions and considers how this is mirrored in current psychotherapeutic practice. It argues that psychotherapists have much to learn from philosophy and that a clear understanding of life events and issues is essential for doing good psychotherapy.